2015
DOI: 10.4081/hr.2015.5704
|View full text |Cite
|
Sign up to set email alerts
|

Central Neurotoxicity of Immunomodulatory Drugs in Multiple Myeloma

Abstract: Immunomodulatory drugs (IMiDs) currently used in the treatment of multiple myeloma, are thalidomide, lenalidomide and pomalidomide. One of the most common side effects of thalidomide is neurotoxicity, predominantly in the form of peripheral neuropathy. We report 6 cases of significant central neurotoxicity associated with IMiD therapy. Treatment with thalidomide (1 patient), lenalidomide (4 patients), and pomalidomide (1 patient) was associated with various clinical manifestations of central neurotoxicity, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…17 We and others reported single-agent activity of lenalidomide in refractory secondary CNS diffuse large B-cell lymphoma (DLBCL) as well as mantle cell lymphoma involving the CNS. 18,19 Given reports of neurotoxicity associated with lenalidomide and other immunomodulatory drugs in the setting of myeloma and other lymphoid malignancies, 20,21 that the direct binding protein and mediator of cellular activity of lenalidomide, cereblon, is highly expressed in neurons in the brain, 22,23 and that it is well-established that CNS lymphoma patients are at high risk for neurocognitive deficits and neurotoxicity, we designed a phase 1 investigation to determine a safe, maximum tolerated dose (MTD) of lenalidomide for this patient population. The rationale for this approach is also supported by the fact that CNS lymphoma patients often have a poor performance status and are particularly vulnerable because of immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…17 We and others reported single-agent activity of lenalidomide in refractory secondary CNS diffuse large B-cell lymphoma (DLBCL) as well as mantle cell lymphoma involving the CNS. 18,19 Given reports of neurotoxicity associated with lenalidomide and other immunomodulatory drugs in the setting of myeloma and other lymphoid malignancies, 20,21 that the direct binding protein and mediator of cellular activity of lenalidomide, cereblon, is highly expressed in neurons in the brain, 22,23 and that it is well-established that CNS lymphoma patients are at high risk for neurocognitive deficits and neurotoxicity, we designed a phase 1 investigation to determine a safe, maximum tolerated dose (MTD) of lenalidomide for this patient population. The rationale for this approach is also supported by the fact that CNS lymphoma patients often have a poor performance status and are particularly vulnerable because of immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…PN of grades 1–2 has been observed in 18%–24% cases, considering also that the majority of these patients had a prior history of PN 8789. Rare cases of central neurotoxicity with IMiDs have been reported 90. New IMiD pomalidomide causes very few incidences of PN; <5% 91,92…”
Section: Treatment-related Pnmentioning
confidence: 99%
“…After the use of Thalidomide, with typical doses ranging from 50 mg to 300 mg/day, the onset of a dose-dependent peripheral sensory neuropathy has been reported, which symmetrically begins from the distal extremities (hands and feet), and which clinically manifests with paresthesia of the extremities [ 113 , 114 , 115 ]. Further studies confirmed that the sensory neuropathy is length-dependent [ 20 , 116 ].…”
Section: Thalidomidementioning
confidence: 99%
“…Since Thalidomide induces a dose-dependent neuropathy, the clinical recommendation is to use the lowest effective dose, with a careful monitoring of electrophysiological parameters which represent the first neuropathic sign, such as the reduction of SNAPs amplitude, to evaluate the drug dose reduction or even the treatment temporary or permanent withdrawal. In addition, preventive strategies such as anti-oxidant or growth factors administration are currently under evaluation [ 117 , 118 ], as well as the use of derivatives with a very low neurotoxic profile, such as Lenalidomide and Pomalidomide [ 113 ].…”
Section: Thalidomidementioning
confidence: 99%